The Determinant of Financial System Stability in Indonesia (Efficient: Indonesian Journal of Development Economics, 2023)
The stability of the financial system in Indonesia is still quite vulnerable to disturbances (shock) from within and outside the country as indicated by a high ratio of NPLs or bad loans. The purpose of this study was to determine and analyze the effect of world crude oil prices as an indicator of external shock, exchange rates, inflation, and the BI rate on financial system stability in Indonesia in the short and long term. This study uses regression analysis of time series data from 2002 to 2020, using the ECM (Error Correction Model) method. The results show that in the short term the variables that affect financial system stability are inflation and BI rate variables, as well as world crude oil prices and variables. The exchange rate has no effect on financial system stability, while in the long term the variables that affect financial system stability are world crude oil prices, exchange rates, and the BI rate, while inflation has no effect on financial system stability.